Intra-arterial Infusion of Autologous Bone Marrow Mononuclear Stem Cells in Subacute Ischemic Stroke Patients - Ghali, Azza Abass; Yousef, Mohamed Khalil; Ragab, Osama AbdAllah; ElZamarany, Enas Arafa (Frontiers in Neurology, 2016)
Introduction: Based on many preclinical and small clinical trial, stem cells can help stroke patient with the possibility of replacing the cells and support the remaining cells. The aim of this study was evaluating the safety and feasibility of bone marrow mononuclear (BMMN) stem cell transplantation in subacute ischaemic stroke patients. Patients and methods: A thirty-nine (n=39) patients with subacute ischaemic cerebral infarct due to large artery occlusion in the middle cerebral artery (MCA) territory were recruited. They were distributed in two groups first group (n=21) served as an experimental whom received intra-arterial mononuclear stem cells (BMMNC), while the other group (n=18) served as a control group. All patients were evaluated clinically by NIHSS, modified Rankin scale (mRS), Barthel Index(BI), Modified and standardized Arabic version of the Comprehensive Aphasia Test and radiological for 12 months. Results: The stem cells treated group showed better improvement but it wasn’t significant when compared with non-treated group. The volume of infarction changes at the end of the study was non-significant between both groups. There was no, or minimal adverse reactions in stem cells treated group. Conclusion: the study results suggest that autologous BMMN stem cell intra-arterial transplantation in subacute MCA ischemic stroke patients is safe with very minimal hazards, but no significant improvement of motor, language disturbance or infarction volume was detected in stem cells treated group compared with the non-treated group. Key words: Stem cell. Ischaemic stroke. Intra-arterial. BM-MNC